Fungal stains on paper: is what you see what you get? - Oliveira Sequeira, Sílvia (2019)
Mitigation of fungal biodeterioration on paper documents and artworks represents a challenge to conservators worldwide. Numerous lists of fungal species have been identified from paper collections, but are those species responsible for the respective biodeterioration phenomena or just environmental contaminants? The present work was aimed at obtaining an association between specific fungal stains and causative fungal species. 23 stains from three paper documents were sampled. Fungal structures observed in situ with optical and scanning electron microscopy were compared with the identification of isolates by molecular biology tools. Correlation between the observed fungal structures and the identified fungal isolates was achieved, varying from 13% to 64% of the samples within the three studied documents. Grey/black and dark brown stains were associated with Chaetomium globosum, C. murorum, Penicillium chrysogenum, P. commune, Myxotrichum deflexum and Stachybotrys chartarum. Eurotium rubrum was isolated from a foxing stain and Penicillium citrinum was identified on light orange stains.   Received: 2018-3-7 Revised: 2018-9-21 Accepted: 2018-10-12 Online: 2018-11-16 Publication: 2019-11-6